The implementation of Maqashid Sharia: heterogeneity of scholars' fatwas towards Islamic banking contracts - Arfan, Abbas; Arfan, Iklil Athroz; Alkoli, Abdulrahman; Ramadhita, Ramadhita (Faculty of Law, University of Muhammadiyah Malang, 2024)
This study aims to analyze the differences in fatwas among scholars in the Middle East and South East Asia (Indonesia and Malaysia) towards various Islamic Banking Contracts products and assess the implementation of maqâshid al-sharia within the variety of fatwas mentioned. This study employed a qualitative approach and fatwas from the Middle East and South East Asia as the primary data, while the secondary data were obtained from books on Muaamalah Fiqh and Islamic Banking. The data were garnered based on a literature review with a content analysis technique. The descriptive-inductive method with a reflective way of thinking is used for data exposure, leading to the following findings: 1) There are differences in fatwas towards three Islamic Banking contracts: a) The determination of the deposit contract in the Middle East is stipulated in a qardh contract in a non-investment account; meanwhile, in South East Asia it is stipulated in a wadiah contract; b) in terms of Murâbahah contract, some of the Middle East scholars forbid it, while, some of South East Asian scholars and few scholars from Middle East allow it, and; c) in terms of the al-Ijarah al-muntahiyyah bi al-tamlik, most of Middle East Scholars forbid it, but South East Asian scholars allow it; 2) The implementation of maqâshid sharia within differences of fatwas among scholars has been appropriately implemented in accordance with Islamic law specified under contracts in Islamic banking products in Muslim countries.